Optimizing regional tax revenue with taxpayer compliance as a moderating variable in Yogyakarta - Putra, Afuan Fajrian; Syahid, Ilham; Riantika, Reny Lia (Journal of Contemporary Accounting, 2025)
This study uses a quantitative approach to test the effect of the quality of tax services and digitalization of tax administration on tax revenues moderated by taxpayer compliance. The population and sample in this study were taxpayers registered with the BPAKD of Yogyakarta City and made regional tax payments. The sampling technique used was probability sampling employing the Cochran formula. Structural Equation Modeling (SEM) based on variants or Partial Least Square (PLS) with the SmartPLS version 4.0 was applied as an analysis tool. The results of this study indicate that the quality of tax services, digitalization of tax administration, and taxpayer compliance have a positive and significant effect on tax revenues. In addition, the quality of tax services and digitalization of tax administration have a positive and significant effect on taxpayer compliance. Taxpayer compliance is proven to successfully mediates the relationship between the quality of tax services, digitalization of tax administration, and tax revenues. This study offers a practical insights for the Yogyakarta City government as a regulator which emphasize the importance of improving the quality of tax services provided to taxpayers and how the digitalization system of tax administration can maximize the potential for regional tax revenues. Moreover, this study contributes to the scientific understanding and expansion of research on regional taxes.